Free space optical front-end receiver's bandwidth enhancement employing micro-electro mechanical systems variable feedback capacitor - Arnidza Ramli, 1984-; Sevia Mahdaliza Idrus Sutan Nameh; Abu Sahmah Mohd. Supa'at; Fakulti Kejuruteraan Elektrik (2010)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2010